2014
DOI: 10.1136/bcr-2014-207562
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced hypocalcaemia with tetany in a patient with hypoparathyroidism

Abstract: SUMMARYAlthough glucocorticoids have a known negative effect on calcium balance, they do not normally cause clinically significant hypocalcaemia. A young woman with postsurgical hypoparathyroidism developed symptomatic hypocalcaemia on two occasions following treatment with intravenous hydrocortisone for allergic reactions. Oral calcium and vitamin D supplementation could not prevent the development of hypocalcaemia. She was treated successfully with intravenous calcium gluconate infusions and discontinuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some clinical situations may destabilize a welladjusted treatment or even hinder a proper control of calcium levels, including gastrointestinal infections, urgent hospitalizations, medications affecting the absorption of nutrients or other medications (orlistat, cholestyramine, and glucocorticoids, among others), as well as conditions associated with spontaneous malabsorption (inflammatory bowel disease, celiac disease, or malabsorption due to other causes) or iatrogenic (such as post-bariatric surgeries) and difficulties in the ingestion of medications by mouth, as seen in wide surgical resections due to laryngeal cancer (2,(118)(119)(120)(121)(122)(123). The metabolic control during pregnancy and lactation in patients with hypoparathyroidism will be discussed in Section 10.…”
Section: Treatment Of Chronic Hypocalcemiamentioning
confidence: 99%
“…Some clinical situations may destabilize a welladjusted treatment or even hinder a proper control of calcium levels, including gastrointestinal infections, urgent hospitalizations, medications affecting the absorption of nutrients or other medications (orlistat, cholestyramine, and glucocorticoids, among others), as well as conditions associated with spontaneous malabsorption (inflammatory bowel disease, celiac disease, or malabsorption due to other causes) or iatrogenic (such as post-bariatric surgeries) and difficulties in the ingestion of medications by mouth, as seen in wide surgical resections due to laryngeal cancer (2,(118)(119)(120)(121)(122)(123). The metabolic control during pregnancy and lactation in patients with hypoparathyroidism will be discussed in Section 10.…”
Section: Treatment Of Chronic Hypocalcemiamentioning
confidence: 99%
“…[10] However, serious hypocalcaemic symptoms should be relieved by intravenous calcium supplementation as quickly as possible. [1116] Moreover, intravenous calcium administration to patients with refractory hypocalcaemia is a major reason for prolonged hospitalization after thyroid surgery. [17]…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative glucocorticoid (GC) treatment may also exacerbate underlying hypocalcemia and hypoparathyroidism in the postoperative period for patients with 22q11DS. Previous research has suggested that in patients with parathyroid dysfunction, GC treatment may induce clinically significant hypocalcemia [ 9 , 10 ]. GC administration may reduce dietary calcium absorption and may also increase renal calcium excretion.…”
Section: Discussionmentioning
confidence: 99%